2006
DOI: 10.1093/jnci/djj019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surgeon Specialty on Processes of Care and Outcomes for Ovarian Cancer Patients

Abstract: Ovarian cancer patients treated by gynecologic oncologists had marginally better outcomes than those treated by general gynecologists and clearly superior outcomes compared with patients treated by general surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
216
3
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 381 publications
(231 citation statements)
references
References 22 publications
5
216
3
7
Order By: Relevance
“…8,9,[14][15][16][17][18] Despite these observations, the proportion of women with newly diagnosed ovarian cancer initially treated by gynecologic oncologists remains below 50% in the United States. 8,10,11 Although the available data is extremely limited, the factors affecting utilization of gynecologic oncology resources at the time of suspected ovarian cancer diagnosis appear to be multifactorial. Muntz and coworkers 19 reported that health maintenance organization physicians were 3 to 4 times less likely to refer patients with complex gynecologic oncology problems after soliciting a curbside consultation compared with private-practice colleagues.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,[14][15][16][17][18] Despite these observations, the proportion of women with newly diagnosed ovarian cancer initially treated by gynecologic oncologists remains below 50% in the United States. 8,10,11 Although the available data is extremely limited, the factors affecting utilization of gynecologic oncology resources at the time of suspected ovarian cancer diagnosis appear to be multifactorial. Muntz and coworkers 19 reported that health maintenance organization physicians were 3 to 4 times less likely to refer patients with complex gynecologic oncology problems after soliciting a curbside consultation compared with private-practice colleagues.…”
Section: Commentmentioning
confidence: 99%
“…7 Although multiple population-based studies have documented that fewer than 50% of ovarian cancer patients in the United States are referred to gynecologic oncologists for surgery, there is surprisingly little data examining the preceding triage phase of the clinical care continuumereferral patterns of women diagnosed with an adnexal mass without a known diagnosis of ovarian cancer. [8][9][10][11] The objective of the current study was to determine the projected impact on referral patterns of patients undergoing surgery for an adnexal mass after initial evaluation by a nongynecologic oncologist using the MIA, CA125, modified-American College of Obstetricians and Gynecologists (ACOG) referral guidelines, and clinical assessment using the combined datasets of 2 previously reported clinical trials of the MIA.…”
mentioning
confidence: 99%
“…[1][2][3][4] Hence, accurate methods to preoperatively characterize the nature of an ovarian tumor are pivotal. In 2008 the International Ovarian Tumor Analysis (IOTA) group described the Simple Rules.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple authors have reported five-year survival rates between 40 and 50% for patients with microscopic residual disease [1,6]. The rate of complete cytoreduction and associated survival has been shown to be both surgeon and institution dependent [7,8]. The radicality of procedures necessary to obtain this state of residuum does not appear to influence outcomes [1,5,9].…”
Section: Introductionmentioning
confidence: 99%